Creating hypertexts. A strategy to foster writing - Clavijo Olarte, Amparo; Quintana Ramírez, Antonio (Íkala, Revista de Lenguaje y Cultura, 2003)
The purpose of this publication is to share an experience of teacher education and research with Colombian teachers of English using hypertext as a strategy to promote creative writing in Spanish as their native language and in English as their foreign language. This exploratory study was part of the interdisciplinary work developed with graduate students of the Masters program in Applied Linguistics in the seminar on Applications of Hypermedia materials in first and second language. The teacher researchers implemented the writing strategy with children and young adults in elementary, secondary and higher education programs. The article also presents a description of how data was collected and analyzed in the creation of hypertexts with students participants. Received 24-04-03 / Accepted: 18-07-03 How to reference this article: Clavijo Olarte, A. & Quintana Ramírez, A. (2003). Creación de hiperhistorias: una estrategia para promover la escritura. Íkala. 8(1), pp. 59 – 78